Development of Tecton Edu Web-Based Learning Media on Ipas Earth Plate Material for Grade V at SDN Rambutan 03 Pagi - Putri, Soya Amelia; Zulfadewina, Zulfadewina (Journal of Educational Sciences, 2025)
Education is essential for a country's progress, including Indonesia. To support the growth of essential student competencies, the Independent Curriculum integrates science and social studies into a unified subject called IPAS. However, observations at SDN Rambutan 03 Pagi revealed that IPAS learning particularly the topic of Earth Plates remains difficult for students to grasp due to conventional and less interactive teaching methods. To tackle this problem, the study seeks to create a website-based learning tool named Tecton Edu, which is developed following the TPACK framework and incorporates the 4C approach (Critical Thinking, Communication, Collaboration, and Creativity). The study employs a Research and Development (R&D) method using the ADDIE model, consisting of five phases: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observation, interviews, and questionnaires, then analyzed using both qualitative and quantitative techniques. The validation results indicated that the media was rated as highly feasible by media experts (87%), material experts (86%), and IT experts (95%). Educators gave a 100% "very feasible" rating, while student responses from small group trials reached 85%, and large group trials 94%, both in the “very feasible” category. Therefore, Tecton Edu is considered highly suitable for use in fifth-grade science learning.